Characterization of protective immune response elicited by a trimeric envelope protein from an Indian clade C HIV‐1 isolate in rhesus macaques. Issue 5 (15th June 2015) - Menon, Veena; Sneha Priya, Rangasamy; Labranche, Celia; Montefiori, David; Mahalingam, Sundarasamy; Kalyanaraman, Vaniambadi S.; Pal, Ranajit
Abstract Background Recent preclinical studies have demonstrated the use of properly folded trimeric HIV‐1 envelope proteins as immunogen for eliciting protecting immune response in macaques. Methods Trimeric gp145 protein of Indian clade C HIV‐1 (93IN101) was characterized for antigenicity by evaluating its binding to sCD4, and several monoclonal antibodies to HIV‐1 by bio‐layer interferometry. Ten macaques were immunized four times with purified gp145 in adjuplex adjuvant, and serum antibodies were characterized for binding to gp145 and neutralization. Immunized macaques were subjected to weekly low‐dose vaginal challenge with SHIV1157‐ipEL‐p for 8 weeks. Results Env protein elicited strong antibody response in macaques. Following challenge, seven of ten immunized macaques resisted challenge, while six of eight control animals were infected. Conclusions Env proteins from a clade C Indian isolate can elicit protective immune response and therefore may be a candidate for inclusion in a multiclade‐based HIV‐1 vaccine.